2019
DOI: 10.3390/en12020239
|View full text |Cite
|
Sign up to set email alerts
|

An Application of the New Environmental Paradigm (NEP) Scale in a Greek Context

Abstract: Measuring and analyzing public perceptions of the environment are becoming core elements in promoting environmental sustainability, which is a key goal to be achieved. The New Ecological Paradigm Scale (NEP) is used as a unidimensional measure of environmental attitudes as it is developed in order to measure the overall relationship between humans and the environment. A high NEP score is associated with high ecocentric orientation. This research aims to measure and analyze citizens’ NEP score in a Greek area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 30 publications
4
83
0
12
Order By: Relevance
“…In previous work, it was found that information attainment, the degree of eco-consciousness and the perceived benefits of green investments are positively associated with accepting additional financial burden for the expansion of RES [24]. In the case of Greece, feasible national energy management from diversified renewables of local abundance is taking place [23,32,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, it was found that information attainment, the degree of eco-consciousness and the perceived benefits of green investments are positively associated with accepting additional financial burden for the expansion of RES [24]. In the case of Greece, feasible national energy management from diversified renewables of local abundance is taking place [23,32,45].…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated a given dataset, which was previously deployed by Ntanos et al [32]. According to the methodology of Ntanos et al [32], the appropriate sample size for the creation of this dataset was calculated to be 376 respondents selected by stratified random sampling with a 95% level of confidence. The stratification was done at the municipal level by using the list of registered voters per municipality for all 27 municipalities of the area of Evia.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, the NEP and climate change beliefs are the variables that will be examined. Based on prior research, a pro-NEP position has been found to be a consistent indicator of environmental concern and behavior [31][32][33]. The NEP has been used as a predictor of energy policy preferences [18] and water policy preferences [34,35].…”
Section: Environmental Values and Beliefsmentioning
confidence: 99%
“…In Europe (EU28) there are more than 1.6 million km of illuminated streets that annually consume approximately 35 TWh) at a cost of $4 billion euro for the public authorities [2]. During the last decade there has been ongoing research activity focused on energy management using various types of renewable energy sources [3][4][5], on recycling [6], on safety [7][8][9][10], and a concentrated effort has been made for making street lighting systems sustainable [11][12][13][14][15][16][17][18][19] and environmentally friendly [20][21][22]. In addition, during the last few years, the issue of avoiding light pollution [23][24][25][26][27][28] has gained importance in technical reports [29] and expert discussions [30].…”
Section: Introductionmentioning
confidence: 99%